2001
DOI: 10.1152/jn.2001.86.4.1644
|View full text |Cite
|
Sign up to set email alerts
|

NR2B-Containing NMDA Autoreceptors at Synapses on Entorhinal Cortical Neurons

Abstract: We have previously shown that presynaptic N-methyl-D-aspartate receptors (NMDARs) can facilitate glutamate release onto principal neurons in the entorhinal cortex (EC). In the present study, we have investigated the subunit composition of these presynaptic NMDARs. We recorded miniature alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor-mediated excitatory postsynaptic currents (mEPSCs), from visually identified neurons in layers II and V of the EC in vitro. In both layers, bath applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
138
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 47 publications
13
138
0
Order By: Relevance
“…This observation is also not unexpected, since NR2A and NR2B subunits have been seen presynaptically (Charton et al, 1999;Conti et al, 1999;Valtschanoff and Weinberg, 2001). Moreover, electrophysiological studies have shown that these presynaptic receptors function as autoreceptors, facilitating glutamate release (Berretta and Jones, 1996;Woodhall et al, 2001). …”
Section: Discussion Nr2b Subunits Occur Both Pre-and Post-synapticallymentioning
confidence: 71%
“…This observation is also not unexpected, since NR2A and NR2B subunits have been seen presynaptically (Charton et al, 1999;Conti et al, 1999;Valtschanoff and Weinberg, 2001). Moreover, electrophysiological studies have shown that these presynaptic receptors function as autoreceptors, facilitating glutamate release (Berretta and Jones, 1996;Woodhall et al, 2001). …”
Section: Discussion Nr2b Subunits Occur Both Pre-and Post-synapticallymentioning
confidence: 71%
“…These results suggest the lack of AP-3 did not alter the rate of fusion pore opening or the number of postsynaptic receptors at excitatory synapses onto CA3 pyramidal cells. In addition, the higher mEPSC frequency in mocha cultures was not affected by the NMDA receptor antagonist 2-amino-5-phosphonovaleric acid (A.S. and J.-C.P., unpublished observations), suggesting it did not reflect a greater activation of presynaptic NMDA receptors (14,15) because of the lack of Zn release from MF terminals in mocha mice (16,17). After 72-h incubation with TeNT, mEPSC frequency in control cultures was reduced by Ϸ84% (to 0.27 Ϯ 0.04 Hz, n ϭ 9; Fig.…”
Section: Increased Basal Release In Mocha and Brefeldin A (Bfa)-treatmentioning
confidence: 96%
“…AMPA-EPSCs were isolated by holding the postsynaptic cell at Ϫ90 mV to block voltage-dependent postsynaptic NMDARs. In addition, postsynaptic NMDARs were blocked pharmacologically in most experiments by loading the postsynaptic cell internally with the NMDA channel blocker (ϩ)-5-methyl-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5,10-imine maleate (MK-801; 1 mM) via the recording pipette (Berretta and Jones, 1996;Woodhall et al, 2001;Humeau et al, 2003;Mameli et al, 2005;Samson and Pare, 2005;V. A. Bender et al, 2006;Corlew et al, 2007), which selectively blocks postsynaptic NMDA currents without affecting NMDA currents in neighboring cells (V. A. .…”
Section: Whole-cell Recordingmentioning
confidence: 99%
“…Of the four types of NR2 subunits, cortical neurons preferentially express NR2A and/or NR2B (Monyer et al, 1994). In cortex, postsynaptic NMDARs undergo an early postnatal developmental switch from NR2B-containing to NR2A-containing receptors (Monyer et al, 1994;Flint et al, 1997;Kew et al, 1998;Stocca and Vicini, 1998;Tovar and Westbrook, 1999;Liu et al, 2004), whereas PreNMDARs are thought to preferentially retain NR2B subunits (Woodhall et al, 2001;Sjöström et al, 2003;Yang et al, 2006). To determine the subunit composition of PreNMDARs at L4 -L2/3 synapses, we applied the antagonist ifenprodil, which blocks NR2B-containing NMDARs (Williams, 1993).…”
Section: Prenmdars Contain Nr2b Subunitsmentioning
confidence: 99%
See 1 more Smart Citation